Measuring the Value of Knowledge Management Practices at Government Research and Development Centers. (20th November 2016) - Mendoza, Cynthia; Bischoff, John; Willy, Christopher
Abstract : During the last decade, many US government research and development centers adopted some type of knowledge management (KM) practice, either as a formal requirement or as part of a KM strategy to drive efficiency and remain competitive in the technology and intellectual capital marketplace. Many of these organizations implemented KM practices within their KM strategies, and many of these KM practices required similar tools and processes. However, KM implementation within the government sector has faced challenges. Some of the KM strategies provided integration of analytics and records management (explicit knowledge), and others addressed values‐based observations, culture change, and sharing of information (tacit knowledge). This paper evaluated productivity as measured by publication rates at selected research and development centers. These rates were evaluated before and after implementation of KM practices to determine if a statistically measurable relationship exists between the adoption of KM practices and comparative productivity values. Results showed that the three centers studied, even with governmental formalities, experienced increases in publication rates in the post‐KM period. Copyright © 2016 John Wiley & Sons, Ltd.